Polemik Rancangan Undang-Undang Anti Pornografi & Pornoaksi (RUU-APP) - Fardiah, Dedeh (Mediator, 2007)
This article focuses on polemics concerning the draft of Anti-pornography Act as represented by two national dailies: Kompas and Republika. Kompas was traditionally perceived as media with strong Christianity values and liberal tendencies. Contrasted with Kompas, Republika is perceived as media which represents Islamic values with strong Islam movement interests. Employing framing analysis devices, it is found that Kompas has defined anti-pornography act polemics as humanity problem. Meanwhile, Republika framed it as national problem to be solved. Concerning the source of problem, Kompas blamed the substance of the draft, whereas Republika blamed the government.